AN EXPLORATORY STUDY INTO EFL TEACHERS AND STUDENTS’ PERCEPTIONS ABOUT THE 2013 CURRICULUM IMPLEMENTATION - Ratih, Dewi; Basikin, Basikin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Since the beginning, the 2013 EFL curriculum has become a center for research in the field of language learning. This can be seen from pro and cons that surround during the implementation. At certain level, the 2013 EFL curriculum has reported facing various issues. These issues, especially, related to the use of predetermined syllabus and textbooks as the main models of learning, reduction in teaching hours, teaching approach, and the authentic assessment. Reflecting from these issues, this study tries to map the implementation of the curriculum in the classroom by appointing to Snyder et al. (1992) approach models. It is conducted by noticing Fullan’s (2007) curriculum implementation factors. The study employs a sequential exploratory method involving twenty-one EFL teachers from five different senior high schools and two hundred-thirteen students. The study reveals that there are two models of approach that are most often applied by EFL teachers. These are mutual-adaptive and fidelity approach model. Eventually, the factors that emerge need to be taken into consideration by policy makers as evaluation material for further language curriculum development.